Estimating a fiscal reaction function to assess Egypt's debt sustainability - Ramadan, Nadin Hossam El Din (AUC Knowledge Fountain, 2020)
This paper assesses Egypt’s debt sustainability using the fiscal reaction function approach, which tests whether the government responds (or not) to debt accumulation with adequate policy reactions to mitigate any kind of shocks. Both econometric models, the Autoregressive distributed lag (ARDL) and the Vector auto regression (VAR), are applied to test for Egypt’s fiscal reaction function. The results of both models show that Egypt’s debt can be sustainable under the period of study since the primary deficit responds negatively to the increase of the debt-to-GDP, implying that there’s fiscal response by the fiscal authorities in Egypt. The GDP growth also shows a statistically significant impact on reducing the primary deficit through both model results. On the other hand, the ARDL results show that an exchange rate depreciation prompts fiscal adjustment possibly to contain the inflationary effects of the devaluation. According to the Bounds and Johansen tests, the results confirm that there’s co-integration among the variables, implying that the series exhibit a long-term equilibrium relation, but with quite a slow rate of mean reversion to equilibrium. The results also reveal that the business cycle is a key long-run determinant of the fiscal stance in Egypt. Following a counter-cyclical fiscal policy, the government seeks fiscal consolidation during boom times and fiscal outlays during recession times.